ANALISIS SITOGENETIK KARIOLISIS EPITEL MUKOSA BUKAL PADA PEKERJA DRY CLEANING DI YOGYAKARTA - , ANNIS SYARIFAH, Prof. Dr. drg. Regina TC. Tandelilin, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dry cleaning is washing procedure using chemical solvent other than water. The most frequent chemical solvent used in dry cleaning is perchloroethylene which is suspected to have toxic property and possibility to poison human body by means of oral ingestion and inhalation. The degree of toxicity of material can be measured by evaluating cellular necrosis in affected tissue. As one of the stages of cellular necrosis, karyolysis is mostly chosen to measure material toxicity since the frequency of karyolysis can describe degree of necrosis. The aim of this study was to evaluate karyolysis frequency in buccal mucosal epithelial cells of dry cleaning workers in Yogyakarta. An exfoliative cytology techniques of buccal mucosal epithel was used to assess karyolysis frequency. Twelve drycleaning workers who have direct and daily exposure to perchloroethylene were chosen for subjects of this study. Twelvestudents of Faculty of Dentistry Universitas Gadjah Mada who didnât have the risk of perchloroethylene exposure were chosen for control group. All subjects swabbedin left side of buccal mucosal epithel with cytobrush. Swabbed specimens were dyed usingFeulgen-Rossenbeck modification technique and evaluated microscopically per 1000 cells. Results of this study showed that karyolysis frequency of buccal mucosal epithelial cells in perchloroethylene exposed group was significantly different compared to control group. It is concluded that there were relationship between perchloroethyleneexposurewithincreasing of karyolysis frequency in buccal mucosal epithelial cells and occur 7 years after exposure significantly.